Clinical Profile and Epidemiology of Neonates Presenting with Acute Gastroenteritis with Special Emphasis on Acute Kidney Injury - Raman Sharma; Vipul Taneja; kajal khajuria; Rasmeen Kaur; AK Bhardwaj (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Acute Gastroenteritis (AGE) is one of the most common causes of hospitalisation in children as well as neonates. According to World Health Organisation (WHO), 80% of deaths due to diarrhoea occur in first two years of life. Acute Kidney Injury (AKI) is one of the most common complications associated with gastroenteritis and dehydration. Neonates constitute major bulk of infant mortality and morbidity. The goal of this study was to identify risk factors, feeding pattern and electrolyte abnormalities in neonates presenting with AGE. Aim: To study the clinical profile and epidemiology of neonates presenting with AGE with special emphasis on AKI. Materials and Methods: A prospective observational study was conducted in the Neonatal Intensive Care Unit (NICU) of Department of Paediatrics between December 2019 to May 2021 at MMIMS Research and Hospital, Mullana, Ambala, Haryana, India. Ethical clearance was obtained from the ethical committee prior to the study. A total of 510 neonates were admitted during this period in NICU. Out of them 151 neonates of AGE who met the inclusion criteria were enrolled in the study. Clinical Data and lab investigations i.e., serum electrolytes and Renal Function Test (RFT) were collected and entered in pretested proforma meeting the objectives of the study. Kidney Disease Improving Global Outcome (KDIGO) was used to diagnose AKI. Results: In this study, out of the 151 patients of AGE, 56 (37.09%) patients developed AKI. Hyperkalaemia in 85 (56.29%) patients was the most common electrolyte abnormality followed by hypernatremia 35 (23.18%). Hyponatraemia was present in only 15 (9.9%) patients. Acidosis was present in 41 (27.15%) patients. Exclusive formula feeding was the single most modifiable risk factor for AKI. Conclusion: It was found that feeding pattern is the most important and modifiable risk factor associated with increased incidence of AGE and AKI in neonates. Exclusive formula fed babies are more prone to AGE due to improper composition of feeds as compared to mixed feeding or exclusive breast feeding. Thus, exclusive breast feeding must be promoted. Hyperkalaemia remained the most common electrolyte abnormality in these patients.